THE ROLE OF LOCAL WISDOM (PIIL PESINGGIRI) IN DERADICALIZATION EFFORTS (International Conference on Social and Islamic Studies, 2022)
Islam, as a religion of rahmatan lil alamin, teaches its people to maintain peace and spread love. However, a narrow understanding of Islam then tends to lead to radicalism. Exclusivity, anti-tolerance, fanaticism, and revolutionary are characteristics of radicalism that have the potential to create a negative stigma in society for the religion of Islam. Therefore, various deradicalization efforts have been carried out, one of which is by practicing a local wisdom approach that is considered capable of countering radicalism through deep-rooted traditions. This study aims to analyze the local wisdom of Lampung Culture, namely Piil Pesinggiri, by focusing on the deradicalization movement through da'wah. This method is instrumental in minimizing radicalism with a local wisdom approach. The values​​of togetherness that the people of Lampung have in Piil Pesinggiri become material for da'wah as an effort to approach an effective deradicalization movement. Although the term deradicalization is not found explicitly in Lampung's cultural philosophy, Piil Pesinggiri, which is a way of life for the people of Lampung, can be juxtaposed with the Islamic da'wah approach as an effort to deradicalize the movement. Piil Pesinggiri's philosophy consists of five values: Pesinggiri, Juluk-Adok, Nemuy-Nyimah, Nengah-Nyappur, and Sakay-Sambayan, each of which is filled with the teachings of moderate and balanced goodness. The meanings of these five values ​​can be conveyed and packaged in da'wah messages, both with the da'wah method bil hal and bil lisan.